(untitled) (MATEMATIKA, 2012)
This paper reports the identification of more-for-less paradox in the linear fractional transportation problem using objective matrix. We characterize the m× n objective matrices of linear fractional transportation problem for which there exist supplies and demands such that the transportation paradox arises. At the end numerical examples are given for explaining the theory. Keywords: Linear fractional transportation problem; more-for-less paradox. 2010 Mathematics Subject Classification: 90C32; 90B06